Improvement of Quality and Quantity of Technology-Based Learning in Pharmacy and Medical Laboratory Technology - Chusna, Nurul; Novaryatiin, Susi; Purbayanti, Dwi; Mulyani, Evi; Ardina, Rinny; Rahmah, Windya Nazmatur; Pratama, Mohammad Rizki Fadhil (Borneo Journal of Medical Laboratory Technology, 2025)
The enhancement of technology-based learning in the fields of pharmacy and medical laboratory technology is imperative to keep pace with advancements in healthcare and educational methodologies. This study investigates the strategies and impacts of integrating cutting-edge technologies into the curricula of these disciplines. Key areas of focus include the implementation of virtual simulations, online learning platforms, and interactive multimedia resources. The research highlights how these technologies improve the quality of education by providing students with realistic, hands-on experiences that enhance their practical skills and theoretical knowledge. Additionally, the study explores the scalability and accessibility of technology-based learning, which contributes to increased student engagement and enrollment. By leveraging data analytics and feedback mechanisms, educators can tailor learning experiences to meet individual student needs, thereby improving learning outcomes. The findings suggest that the thoughtful integration of technology not only enriches the educational experience but also prepares students more effectively for the evolving demands of the healthcare industry. This research underscores the necessity of continuous investment in educational technologies to sustain the quality and quantity of learning in pharmacy and medical laboratory technology programs.